Der Raum is kein empirischer Begriff. Zu Kants erstem Raumargument - Heidemann, Dietmar H (Con-Textos Kantianos. International Journal of Philosophy, 2018)
„The paper discusses Kant’s first argument from space in the „Critique of pure Reason”. It argues that, contrary to what parts of the literature have claimed, the argument provides convincing reasons for the view that in order to locate objects in space outside us we must already presuppose the idea of space such that it cannot be borrowed from the objects perceived in space. The paper shows how the argument can be made transparent not only by clarifying Kant’s usage of “distinct from” and “ausser uns” but also by retracing its main idea back to the 1768 essay “Concerning the Ultimate Foundation of the Differentiation of Regions in Space” and its incongruent counterparts argument.”